Distribution and antimicrobial susceptibility of Vibrio species associated with zooplankton in coastal area of Korea. Issue 1 (15th December 2017) - Yang, Ji Hye; Mok, Jong Soo; Jung, Yeoun Joong; Lee, Ka Jeong; Kwon, Ji Young; Park, Kunbawui; Moon, Seong Yong; Kwon, Soon Jae; Ryu, A Ra; Lee, Tea Seek
Abstract: Vibrio parahaemolyticus and V . vulnificus are the most common pathogens causing seafood-borne illnesses in Korea. This study determines the abundance and antimicrobial resistance of pathogenic Vibrio species in seawater and zooplankton samples from the Geoje Island coast in Korea, which is an important area for coastal fisheries, the fishing industry, and tourism. The two Vibrio species were detected more in mesozooplankton samples than in seawater samples. V . parahaemolyticus isolates showed greater resistance than those of V . vulnificus for antimicrobials. Of V . parahaemolyticus isolates, 93.3% exhibited resistance to three or more antimicrobial agents. Conversely, more than 80% of V . vulnificus isolates showed susceptibility to all antimicrobials examined, with the exception of rifampicin. Our findings show that strong antimicrobial resistance of V . parahaemolyticus in the surveyed area was exposed to conventionally used antibiotics, therefore necessitating proper surveillance programs for the monitoring of antimicrobial resistance patterns in seawater bodies and aquatic animals. Highlights: Survey area is an important for coastal fisheries, the fishing industry, and tourism. Pathogenic Vibrio strains were detected more in mesozooplankton than in seawater. V . parahaemolyticus exhibited greater antimicrobial resistance than V . vulnificus . 93.3% V . parahaemolyticus isolates showed resistance to three or more antimicrobials.